PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN NUMERASI DALAM PEMBELAJARAN MATEMATIKA - Dayat Mardiana; Lukman Nulhakim; Sudirman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine students' mathematical numeracy abilities before and after the implementation of the Project Based Learning (PjBL) learning model assisted by learning video media. This type of research is experimental research with a quantitative approach. The research sample used was Class V-B students of SDN 1 Giriharja, Cipanas District, consisting of 25 students and taken using saturated sampling techniques. This study used a data collection technique, namely a written test in the form of a mathematical numeracy ability test sheet. Data analysis used a t-test. The results of the study showed that (1) Mathematical numeracy abilities before the implementation of the PjBL learning model assisted by learning video media were included in the moderate category based on the results of the mathematical numeracy ability pre-test with an average of 23.00. (2) Mathematical numeracy abilities after the implementation of the PjBL learning model assisted by learning video media were included in the moderate category based on the results of the mathematical numeracy ability post-test with an average of 80.60. (3) There was a significant influence of the implementation of the PjBL learning model assisted by learning video media on students' mathematical numeracy abilities based on the results of statistical tests that showed a Sig. value. 0.000 < 0.05 with a significance level of 5%. Thus, it can be concluded that the implementation of the Project Based Learning learning model assisted by learning video media has an effect on students' mathematical numeracy abilities.